Strong Evidence of a Phosphanoxyl Complex: Formation, Bonding, and Reactivity of Ligated Phosphorus Analogues of Nitroxides. Issue 46 (13th October 2016) - Heurich, Tobias; Nesterov, Vitaly; Schnakenburg, Gregor; Qu, Zheng‐Wang; Grimme, Stefan; Hazin, Khatera; Gates, Derek P.; Engeser, Marianne; Streubel, Rainer
Abstract: Facile access to [W(CO)5 (Ph2 P‐OTEMP)] is used to initiate a study on the generation, properties, and reactions of transient phosphanoxyl complexes [ML n (R2 PO)], the first example of which could be trapped via heterocoupling with the trityl radical. It is also demonstrated that the phosphorus nitroxyl complex acts as radical initiator in the polymerization of styrene. The quest for P−O versus O−N bond homolysis, as well as the initial steps of the polymerization were studied by DFT methods. Abstract : Build up to break : P ‐OTEMP phosphane metal complexI preferentially undergoes homolytic O−N bond cleavage forming the transient phosphanoxyl complexII . DFT calculations provide insight into the formation ofI as well as into the homolysis processes ofI and the trapping reactions ofII .